2022
DOI: 10.1091/mbc.e21-11-0558-t
|View full text |Cite
|
Sign up to set email alerts
|

ER-localized phosphatidylethanolamine synthase plays a conserved role in lipid droplet formation

Abstract: The asymmetric distribution of phospholipids in membranes is a fundamental principle of cellular compartmentalization and organization. Phosphatidylethanolamine (PE), a nonbilayer phospholipid that contributes to organelle shape and function, is synthesized at several subcellular localizations via semi-redundant pathways. Previously, we demonstrated in budding yeast that the PE synthase Psd1, which primarily operates on the mitochondrial inner membrane, is additionally targeted to the ER. While ER-localized Ps… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…In M. oryzae, the involvement of PE biosynthesis in virulence may be through the regulation of the degradation and utilization of lipid droplets and glycogen during appressorium formation, which we showed are impaired in the Mopsd2 mutant (Fig. 1g, h) (Gok, et al, 2022). Deletion of MoFAS1, a gene encoding a fatty acid-degrading enzyme, results in defective melanin biosynthesis and impaired utilization of lipid droplets in M. oryzae, consistent with Mopsd2 (Sangappillai & Nadarajah, 2020).…”
Section: Discussionsupporting
confidence: 80%
“…In M. oryzae, the involvement of PE biosynthesis in virulence may be through the regulation of the degradation and utilization of lipid droplets and glycogen during appressorium formation, which we showed are impaired in the Mopsd2 mutant (Fig. 1g, h) (Gok, et al, 2022). Deletion of MoFAS1, a gene encoding a fatty acid-degrading enzyme, results in defective melanin biosynthesis and impaired utilization of lipid droplets in M. oryzae, consistent with Mopsd2 (Sangappillai & Nadarajah, 2020).…”
Section: Discussionsupporting
confidence: 80%
“…In M. oryzae , the involvement of PE biosynthesis in virulence may be through the regulation of the degradation and utilization of lipid droplets and glycogen during appressorium formation, which we showed are impaired in the Mopsd2 mutant (Fig. 1g,h) (Gok et al ., 2022). Deletion of MoFAS1 , a gene encoding a fatty acid‐degrading enzyme, results in defective melanin biosynthesis and impaired utilization of lipid droplets in M. oryzae , consistent with Mopsd2 (Sangappillai & Nadarajah, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies in yeast and mammals reported the presence of the PS decarboxylase enzyme PISD1 in ER subdomains where LD biogenesis occurs [99,100]. In human cells, Kumar et al revealed the existence of a second isoform of PISD that, instead of being localized to the mitochondrial inner membrane as the main isoform, is localized to the ER-derived LD.…”
Section: Mam and Mitochondrial Protein Interplay For Lipid Transfer A...mentioning
confidence: 99%